NEAR RINGS ADMITTING CERTAIN DECOMPOSITION THEOREMS (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
In the present paper we shall investigate some decomposition theorems for near rings satisfying any one of the conditions; (1)  (2)whereare integers.